Antiquité tardive: construction et déconstruction d’un modèle historiographique - Athanassiadi, Polymnia (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2007)
Abstract The concept of Late Antiquity as an autonomous historical period was launched in the 1970s and has been gaining ground ever since. The chronological, geographical and epistemological expansion of its boundaries goes hand in hand with an optimistic historical vision: the era which was previously known as “an age of anxiety” has become “an age of ambition.” Its hero is the holy man – a new sociological type whose power in this world and the next endows the society from which he emerges with a remarkable dynamism. Born of a reaction to the historiographical model of crisis and decline, which corresponds to the tripartite periodisation “Antiquity, Middle Ages, Modern Times”, the postmodern concept of a long, autonomous, dynamic and multi-cultural Late Antiquity is now in its turn the subject of a reaction. The new millennium has seen the beginnings of a return to the study of the political, administrative and economic structures of the end of the ancient world, and, perhaps inevitably, to a more traditional, and therefore a more sombre view of this period. After analysing the main stages in the debate between these two fundamental positions, and evoking its ideological background, the article argues for a Late Antiquity which is autonomous but fluid – an interval between two entities, Antiquity and the Middle Ages, during which a society centred on Man mutated into one constituted for the greater glory of God. It further suggests that the explanation as to how an anthropocentric culture was transformed into a theocracy should be sought in the area of religion with all its parameters (social, psychological and especially theological), and that the interpretative tool for such an analysis should be the concept of violence, both physical and intellectual.